Analysis of Service Quality on Visitor Satisfaction at California Cialam Jaya Agrotourism Site, Tanea Village, Konda Subdistrict, South Konawe Regency - Sumiyati; Gafarudin, Abdul; Sadimantara, Fahria Nadiryati (International journal of technology and education research, 2026)
This study aims to analyze the quality of service on visitor satisfaction at California Cialam Jaya Agrotourism, Tanea Village, Konda District, South Konawe Regency. This study uses a quantitative descriptive method with the Importance Performance Analysis (IPA) approach. The research sample consisted of 44 respondents obtained through accidental sampling techniques. Data were collected through distributing questionnaires that measured five dimensions of service quality, namely: tangible (physical evidence), reliability, responsiveness, assurance, and empathy. The results of the study indicate that the level of satisfaction with the performance of the quality of service of Agowisata California Cialam Jaya is in the